ANALISIS KECUKUPAN MATERI KURSUS CALON PENGANTIN - Nur Khafidhoh Khafidhoh; Rizki Amelia (Midwifery Care Journal, 2021)
The high rate of maternal and infant mortality and the difficulty of AKI and AKB to decrease indicate that maternal health program interventions cannot only be carried out in the downstream part, namely for pregnant women, but also should be drawn upstream in the group of adolescents and young adults to ensure individuals can grow and develop healthy. Today, reproductive health problems in adolescents have not been fully addressed. This can be seen from the still high age of marriage, which amounted to 46.7% ( (Kemenkes, 2010)[i]) and still high births in adolescence (ASFR), which amounted to 48 per 1000 women (IDHS, 2012). Teenagers' knowledge of reproductive health is also still low and the incidence of pregnancy at adolescence is still high at 16.7%. Even though the implementation of thin bride and groom has been carried out by the Ministry of Religion in collaboration with the Health Office.This research is a qualitative descriptive study that will look at how the curriculum is applied in implementing the bride and groom courses, especially the curriculum on reproductive health and pregnancy preparation. The technique of collecting data by indept interview to the Ministry of Religion, DKK and Puskesmas will then be triangulated to prospective brides who have received a bride and groom course. Data will be analyzed using content analysis.The results of the study show that the material that must be delivered is not in accordance with the existing time allocation, there are variations in the implementation of catin class counseling